Photo-induced effects in Ge25Ga10S65 glasses studied by XPS and XAS - Lisboa Filho, Paulo Noronha [UNESP]; Mastelaro, V. R.; Schreiner, W. H.; Messaddeq, S. H.; Li, M. S.; Messaddeq, Younes [UNESP]; Hammer, Peter [UNESP]; Ribeiro, SJL; Parent, P.; Laffon, C. (Elsevier B.V., 2005)
The present paper focuses on the structural, electronic, and compositional properties of Ge25Ga10S65 glasses before and after UV illumination in air using X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS) techniques. The XPS Ge 3d spectra reveal the existence of Ge-O bonds in the surface region of illuminated glass. In the case of this sample, XAS O K-edge spectra showed the formation of an enriched region of oxygen atoms in the glass bulk, indicating a different bonding structure of oxygen at the surface and in the bulk of the glass. Moreover, the structural changes that occur after UV illumination in the glass sample are identified as the formation of a homogeneous germanium oxide surface layer followed by an intermediary Ge25Ga10S65-yOz subsurface region. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chalcogenide glasses; photo-induced effects; oxygen; XPS; XAS